The Influence of Collaborative Learning Model on Students' Communication Ability in Natural Science Lessons at MI Al Hikmah - Kurniawati , Evi; Farida (MANDAILING GLOBAL EDUKASIA, 2024)
The collaborative learning model aims to maximize the process of cooperation that takes place naturally between students and appreciate the importance of the social context for the learning process. Based on that, the author defines the problem formulation as follows: (1) How is the implementation of the collaborative learning model for class V students in the IPA MI Al Hikmah Masangan Bungah Gresik curriculum? (2) How is the communication ability of class V students in the IPA MI Al Hikmah Lessons Bungah Gresik? (3) How does the implementation of the collaborative learning model influence the communication skills of class V students in the IPA Lessons Al Hikmah Bungah Gresik? As for this research, it was conducted to find out whether or not there is an influence of the collaborative learning model on IPA communication skills. In this research using a quantitative approach with a quasi-experimental type of research. The population of this research is the entire V MI Al Hikmah Masangan class. The sample is determined through the Total Sampling technique. Based on the technique, VA class was obtained as an experimental class while VB class was a control class. The data collection technique uses an essay test. Data were analyzed using hypothesis testing (t test). The results of the research show that the IPA communication ability of students taught with the Collaborative Learning Model is higher than the IPA communication ability of students taught with the conventional learning model. The IPA communication ability in the experimental class (VA) with the Collaborative Learning Model obtained a posttest average of 76.9, while in the control class (VB) with the conventional learning model, the posttest average was 63.25. Based on the results of the hypothesis testing obtained thitung > ttabel ie 7.41 > 2.024 at the level of significance ???? = 0.05. This means that the hypothesis in this research can be accepted and it is stated that there is a positive and significant influence from the use of the Collaborative Learning Model on the communication skills of V class MI Al Hikmah Masangan students in IPA subjects.